2020
DOI: 10.3390/ijms21249726
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics and Osteogenic Differentiation of Ovine Bone Marrow Derived Mesenchymal Stem Cells Stimulated with FGF-2 and BMP-2

Abstract: Cell-based therapies using mesenchymal stem cells (MSCs) are a promising tool in bone tissue engineering. Bone regeneration with MSCs involves a series of molecular processes leading to the activation of the osteoinductive cascade supported by bioactive factors, including fibroblast growth factor-2 (FGF-2) and bone morphogenetic protein-2 (BMP-2). In this study, we examined the biological characteristics and osteogenic differentiation potential of sheep bone marrow MSCs (BM-MSCs) treated with 20 ng/mL of FGF-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 57 publications
(55 reference statements)
2
34
0
Order By: Relevance
“…In particular, the BMP signaling pathway plays a crucial role in the differentiation of MSCs into the osteochondroprogenitor cells [53], after which they allow the differentiated osteoblasts to secrete the bone formatting matrix [54]. Moreover, BMPs have been shown to increase the expression of osteogenic markers in MSCs, including the early osteogenic markers alkaline phosphatase (Alp), Runtrelated transcription factor 2 (Runx2), osterix (Osx), and type I collagen (ColI) and the late markers osteopontin (Opn) and osteocalcin (Ocl) [53,[55][56][57]. Currently, BMP-2 (Medtronic) and BMP-7 (Stryker Biotech) are approved by the Food and Drug Administration (FDA) and available for clinical use in a recombinant form for bone fracture treatment and intervertebral disk regeneration enhancement [57].…”
Section: Cytokines Growth Factors and Signaling Pathways Enhancing Osteogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the BMP signaling pathway plays a crucial role in the differentiation of MSCs into the osteochondroprogenitor cells [53], after which they allow the differentiated osteoblasts to secrete the bone formatting matrix [54]. Moreover, BMPs have been shown to increase the expression of osteogenic markers in MSCs, including the early osteogenic markers alkaline phosphatase (Alp), Runtrelated transcription factor 2 (Runx2), osterix (Osx), and type I collagen (ColI) and the late markers osteopontin (Opn) and osteocalcin (Ocl) [53,[55][56][57]. Currently, BMP-2 (Medtronic) and BMP-7 (Stryker Biotech) are approved by the Food and Drug Administration (FDA) and available for clinical use in a recombinant form for bone fracture treatment and intervertebral disk regeneration enhancement [57].…”
Section: Cytokines Growth Factors and Signaling Pathways Enhancing Osteogenesismentioning
confidence: 99%
“…They can stimulate osteoblast proliferation, promote differentiation into the osteogenic cell lineage, as well as induce angiogenesis [59]. Studies showed that FGF-2 and BMP-2 could act synergistically in bone regeneration, enhancing the effectiveness of bone formation [56,60,61].…”
Section: Cytokines Growth Factors and Signaling Pathways Enhancing Osteogenesismentioning
confidence: 99%
“…The combination of FGF-2 and BMP-2 has already been tested at various concentrations and kinetics actions. A recent in vitro study suggests that sheep BMSCs supplemented with 20 ng/mL of FGF-2 and 100 ng/mL of BMP-2 may be a feasible cellular therapy for bone regeneration [233]. In vivo, the association of 10 µg of FGF-2 and 10 µg of BMP-2 in transfected human MSCs yielded a significantly increased bone regeneration of critical size calvarial defects of nude mice [234].…”
Section: Bmp-2: An Interesting Cytokine For Combined Treatmentsmentioning
confidence: 99%
“…The most abundant fibroblast growth factors in normal adult tissues are FGF-1 and FGF-2. FGF-2 has a stronger mitotic promoting effect (Marquez et al, 2017;Gromolak et al, 2020;Sedlar et al, 2021), and can effectively promote the proliferation of stem cells in the process of tendon repair (Ide et al, 2009;Tokunaga et al, 2015;Guo et al, 2020). Previous reports have proved the effect of FGF-2 on the regeneration of tendons and other soft tissues (Tokunaga et al, 2015;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%